Pengaruh Penggunaan Media Pembelajaran Bahasa Indonesia di Sekolah Dasar - Roisyatul Izza (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2024)
The aim of this research is to determine the effect of using Indonesian language learning media in elementary schools. Indonesian has a very important position and function for the daily lives of elementary school students. Therefore, Indonesian language learning in elementary school needs to be optimized, one of which is the use of media. The use of Indonesian language learning media in elementary school makes it easier to achieve Indonesian language learning goals, especially in language skills. This research uses a qualitative approach with a literature review method. The data collected and analyzed all come from literature and other documentation materials, such as articles in journals, as well as other media that are relevant and are still being studied. So, by using a qualitative approach to this literature study method, it can be seen that there is an influence on the use of Indonesian language learning media used in elementary schools. The benefit of this research is that readers can find out the important role of media in learning Indonesian in elementary school.